Comparative analysis of language and education policies for indigenous minorities in Australia and Malaysia - Renganathan, S. (Eastern University, 2018)
This paper examines the implication of language and education policies for the indigenous minority populations in two contrasting multicultural and multilingual post-colonial nations, Australia and Malaysia. By comparing and contrasting ethnolinguistic and educational policies in these two diverse nations, this paper explores how indigenous minorities have been positioned within each nation's quest for meeting the challenges of becoming multilingual and multicultural nations. The authors argue that although both countries promote multicultural ideals, they fall short in their acknowledgement of the dignity of difference for their indigenous communities. The authors assert that educational and language policies for indigenous peoples must acknowledge the importance of difference and therefore include indigenous cultural ways of knowing, being, and doing to achieve successful educational outcomes. Â© 2018, by International Journal of Multicultural Education.